Flexural buckling behaviour and residual resistances of hot-rolled stainless steel channel section columns after exposure to elevated temperatures - Li, Shuai (2023)
This paper presents experimental and numerical studies on the flexural buckling behaviour and residual resistances of hot-rolled stainless steel channel section columns after exposure to elevated temperatures ranging from 30 ℃ to 1000 ℃. An experimental programme, including heating, soaking and cooling of specimens as well as post-fire initial geometric imperfection measurements and fourteen pin-ended column tests, was firstly performed. The test procedures and results, including failure loads, load–deformation curves and failure modes, were reported in detail. Both ‘C’-shaped flexural buckling (with failure specimens buckling towards webs) and ‘reverse C’-shaped flexural buckling (with failure specimens buckling towards flange tips) were observed upon testing. The experimental programme was followed by a numerical modelling programme, where finite element models were developed and validated against the test results and used to conduct parametric studies to generate additional numerical data over a wide range of cross-section dimensions and member effective lengths. Due to the absence of design standards for stainless steel structures after exposure to elevated temperatures, the relevant ambient temperature buckling curves, as specified in the European code and American specification, were evaluated, using post-fire material properties, for their applicability to hot-rolled stainless steel channel section columns after exposure to elevated temperatures. The evaluation results revealed that the codified ambient temperature buckling curves in combination with post-fire material properties resulted in accurate and consistent post-fire residual resistance predictions for hot-rolled stainless steel channel section columns with ‘C’-shaped flexural buckling, but marginally conservative post-fire residual resistance predictions for their counterparts with ‘reverse C’-shaped flexural buckling.